Implementation of recombinant anti-herpes zoster vaccination in people living with HIV: a single-center experience - Trentacapilli, Benedetta; Raccagni, Angelo Roberto; Diotallevi, Sara; Nozza, Silvia; Lolatto, Riccardo; D’Amelio, Anna Carole; Catalano, Gaia; Ponta, Giacomo; Spagnuolo, Vincenzo; Cernuschi, Massimo; Gianotti, Nicola; Castagna, Antonella; et al. (Frontiers in Virology, 2025)
People living with HIV (PLWH) are at high risk of herpes zoster (HZ). The recombinant anti-HZ vaccine (RZV), approved by European Medicines Agency (EMA) in 2018, has been shown to be effective and safe in PLWH. This study aims to describe the implementation of RZV in our center. Prospective cohort study on PLWH in care at the Infectious Diseases Unit of San Raffaele Hospital, Milan, Italy, receiving RZV between January 2022 and October 2023. To establish three priority criteria for identifying three groups among PLWH and to implement a proactive approach by offering immediate on-site vaccination during routine HIV medical visits. The three priority criteria identified were PLWH older than 65 years, PLWH had at least one previous episode of HZ, and PLWH had a CD4+ T lymphocytes count <200 cells/microL. Among the 599 PLWH vaccinated, 287 (48%) belonged to the Priority Group. The prioritization strategy facilitated the immunization program. The different implementation strategies showed different degrees of success. On-site vaccination during routine HIV medical examinations and prioritization of specific groups are effective strategies to increase vaccine uptake. We believe that collaboration between motivated clinicians and individuals paves the way for opportunities for prevention. These methods are crucial for ensuring effective prevention as new vaccines are introduced.